The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jctc.0c00336
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Coupled-Cluster Singles and Doubles on Modern Stream Processing Architectures

Abstract: We develop a new implementation of coupled-cluster singles and doubles (CCSD) optimized for the most recent graphical processing unit (GPU) hardware. We find that a single node with 8 NVIDIA V100 GPUs is capable of performing CCSD computations on roughly 100 atoms and 1300 basis functions in less than 1 day. Comparisons against massively parallel implementations of CCSD suggest that more than 64 CPU-based nodes (each with 16 cores) are required to match this performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…The SOS‐MP2 method 86 neglects exchange‐like terms to arrive at a formal scaling of O (N 4 ), and THC‐SOS‐MP2 further reduces this scaling to O (N 3 ). Recently, a GPU‐accelerated coupled‐cluster code has also been implemented in TeraChem, enabling coupled‐cluster singles and doubles (CCSD) as well as any method that can be written as a subset of CCSD diagrams 87 …”
Section: Single Reference Post‐scf Methodsmentioning
confidence: 99%
“…The SOS‐MP2 method 86 neglects exchange‐like terms to arrive at a formal scaling of O (N 4 ), and THC‐SOS‐MP2 further reduces this scaling to O (N 3 ). Recently, a GPU‐accelerated coupled‐cluster code has also been implemented in TeraChem, enabling coupled‐cluster singles and doubles (CCSD) as well as any method that can be written as a subset of CCSD diagrams 87 …”
Section: Single Reference Post‐scf Methodsmentioning
confidence: 99%
“…Dr. Hohenstein then discussed an implementation of CCSD and EOM-CCSD algorithms on graphics cards, which makes the calculation of 100 atom systems computationally feasible. The CCSD calculations on eight graphics cards matched the performance of sixty-four 16-core CPU-based nodes …”
Section: Introductionmentioning
confidence: 99%
“…14,15 They have, for instance, demonstrated that NCIs are strongly attenuated in a solvated environment. 16 Despite the intense efforts associated with developing a posteriori dispersion corrections [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] or with reducing the cost of wavefunction-based methods, [35][36][37][38][39][40][41] the finite-temperature description of competing NCIs remains coarse if the solvent is represented as a continuum. In particular, interaction energies estimated by dispersion-corrected computations in implicitly modeled solvent can be one magnitude larger than experimental energies in solutions.…”
Section: Introductionmentioning
confidence: 99%